The PROSES PRODUKSI LAGU DIVERT DALAM INDUSTRI MUSIK INDIE KARYA FALLEN ROSE BAND LOKAL ASAL SURABAYA - Rachell Sevilya Putri; senyum sadhana (Jurnal Pendidikan Sendratasik, 2026)
Fallen Rose is a local band from Surabaya with an alternative rock subgenre and stands independently without being under the auspices of a record label. One of the works produced by the band is the song "Divert", which was produced independently using a home recording concept to maintain its existence. This study aims to describe the production process of the song "Divert" as well as the publication and marketing efforts carried out by Fallen Rose in the independent music industry. The study uses a qualitative descriptive method. Data were obtained through observation, interviews, documentation, and literature studies. The research sources consisted of Dirham Satia as the songwriter and leader of Fallen Rose, Hayyan Sabitah as a sound engineer, Akmal as a creative idea provider, and Harlan as an indie music lover. The results of the study show that the production process of the song "Divert" went through three main stages, namely pre-production, production, and post-production. The pre-production stage includes song creation, musical concept development, and technical preparation of production. The production stage was carried out through the processes of tracking, recording, editing, and the use of the Digital Audio Workstation (DAW) Studio One. The post-production phase includes mixing, mastering, digital distribution, and publication through various social media platforms and music streaming services. Fallen Rose's marketing strategy leverages digital media, the music community, and live performances at various independent music events. Research findings indicate that independent music production allows musicians to have full control over their work and is an effective alternative to the evolving digital music industry.